Recycling, Producer Responsibility and Centralized Waste Management - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 1999)
This paper examines a Waste Management Organisation's (WMO) pricing options to implement the Pareto-efficient allocation in an economy where materials are first extracted, then used for producing a consumption good and finally recycled or landfilled. The WMO is established by the producers who are responsible for the proper disposal of consumption waste which consists of a mix of materials. That mix forms an aspect of the Producers' (green) product design and effects the productivity of secondary material generation. The most favorable pricing strategies are shown to comprise (positive or negative) fees on producers based on residuals and material inputs.
Keywords: H21; Q28; 330; Kreislaufwirtschaft; Produkt-Recycling; Ressourcenökonomik; Allokationseffizienz; Abfallpolitik; Betriebliche Preispolitik; Umwelthaftung; Produktpolitik; Öko-Produkt; Theorie